2014
DOI: 10.1187/cbe.14-06-0108
|View full text |Cite
|
Sign up to set email alerts
|

A Campus-Wide Study of STEM Courses: New Perspectives on Teaching Practices and Perceptions

Abstract: Teachers observed 51 university-level science, technology, engineering, and mathematics (STEM) courses and collected information on the active-engagement nature of instruction. These results give a comprehensive view of the diversity of STEM instruction and student in-class behavior at a campus-wide level. The authors discuss how these results could be used to design targeted professional development.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
160
5
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(171 citation statements)
references
References 35 publications
3
160
5
3
Order By: Relevance
“…Overall, faculty reported that 80% of class time was devoted to lecture. Studies by Lammers and Murphy (2002) and Smith, Vinson, Smith, Lewin, and Stetzer (2014), both of which compared survey responses to observations of classroom practice, concluded that both instructor estimates and observed practices were in high agreement and lecture remains the primary method of instruction at the universities studied.…”
Section: Using This Breakdown We Analysed Survey Responses Related Tmentioning
confidence: 97%
See 2 more Smart Citations
“…Overall, faculty reported that 80% of class time was devoted to lecture. Studies by Lammers and Murphy (2002) and Smith, Vinson, Smith, Lewin, and Stetzer (2014), both of which compared survey responses to observations of classroom practice, concluded that both instructor estimates and observed practices were in high agreement and lecture remains the primary method of instruction at the universities studied.…”
Section: Using This Breakdown We Analysed Survey Responses Related Tmentioning
confidence: 97%
“…In her review of the literature, Newmann (2001) concluded that disciplinary culture and knowledge have a direct impact on the decisions faculty make about teaching practices. In addition, several studies have found a positive relationship between class size and the use of lecture (Lammers & Murphy, 2002;Smith et al, 2014;Thielens, 1987). However, Smith et al (2014) studied only STEM disciplines and found a wide range of teaching practices were employed to supplement lecture in both large and small enrolment courses.…”
Section: Using This Breakdown We Analysed Survey Responses Related Tmentioning
confidence: 99%
See 1 more Smart Citation
“…The application of Rasch measurement in the social sciences has been most notably discussed in the 1967 Invitational ETS conference and in a wide-variety of subsequent publications (Andrich 1978;Boone et al, 2011;Choppin 1985;Libarkin and Anderson 2005;Linacre 1998Linacre , 2006Linacre , 2010Siegel and Ranney, 2003;Smith 1991;Tong 2012;Wilson and Adams 1995;Wright and Stone 1979;Wright 1977Wright , 1984. Rasch modeling is both norm-referenced (comparing individuals to the group) and criterionreferenced (measured according to specific standards; Siegel and Ranney 2003).…”
Section: Quantitative Instrumentmentioning
confidence: 99%
“…A recent, comprehensive meta-analysis (Freeman et al 2014) indicates that student learning is substantially increased and the drop-out rate decreased in STEM courses that devote class time to "active learning" through student-centered instructional techniques, such as clicker questions with peer discussion and other group activities requiring analytical thinking (Mazur 1997;Wood 2004;Vickrey et al 2015). Although systematic collection of data on undergraduate faculty instructional practices is still in its infancy (Wieman and Gilbert 2014), recent surveys and observation studies show that STEM faculty are gradually moving toward supplementing or replacing lectures with active-learning activities in their classrooms (Eagan et al 2014;Smith et al 2014;Lewin et al 2016). …”
Section: A Growing Awareness Of Problems With Traditional Instructionmentioning
confidence: 99%